Update and Confirmation of the Boundary Map for Braja Yekti Village, Braja Selebah Subdistrict, East Lampung Regency - Hermawan, Adinda Putri; Aziz, Al; Zayyan, Azra Aqila; Ajiningtyas, Hanindya Janitra; Safitri, Merlin Susan Norya; Dwiardito, Refrizar; Sinurat, Samuel Guruh Prayuda (Indonesian Journal of Community Services Cel, 2024)
The Community Service Program (KKN) was carried out as a community service activity implemented in Braja Yekti Village. This program aims to improve the previous village map because there was a discrepancy between the map and the original area and to improve the quality of village development planning through accurate mapping of infrastructure and natural resources which makes "village map making" one of the main work programs to support village development planning. The method used in community service is a qualitative approach with a descriptive-explanatory model, and data is obtained through field surveys with the local hamlet head. The stages of this program begin with discussions with village officials to determine the type of map to be made and scheduling a survey with the hamlet head. The implementation stage involves a survey of hamlet boundaries carried out directly in the field. Furthermore, the post-implementation stage includes the creation of a village map in A0 format that displays the survey results in detail. The results of this program show that village maps can be an important instrument in facilitating communication between the village government and the community, while encouraging more effective and efficient development planning. From the results of the evaluation carried out through questions and answers, the implementation of this village mapping work program shows great potential to provide long-term positive impacts on village development and community welfare in Braja Yekti Village.